Phân tích cầu tiêu dùng đồ uống có cồn tại Việt Nam - Phạm Thành, Thái; Nguyễn Văn, Huy (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2021)
This paper aims to estimate demand functions and calculate demand elasticities for alcoholic beverages in Vietnamese households. The current work used the AIDS (Almost Ideal Demand System) system demand function with a data set of the Vietnam Household Living Standards Survey 2018. The AIDS demand function was estimated using the Seemingly Unrelated Regression (SUR) method. Research results showed that consumer demand for alcoholic beverages was sensitive to their price. Also, alcoholic drinks were not luxury goods, and they were substituted products. Light liquor drinks were consumed mainly in urban and high-income households, while rural regions consume much brandy. The excise tax rates should be increased for these products to reduce alcohol consumption and its negative impacts.